Income Recovery of Metal Craftsmen Affected by Covid 19 in Bogor District - Bayu Adhi Prakosa; Meita Arifany; Ade Hendri Hendrawan; Andi Eko Kristus Pramuko (LPPM UIKA Bogor, 2023)
Increasing cases of COVID-19 are affecting metal craftsmen in small and medium enterprises in Tarikolot Village, Bogor Regency, Indonesia. There is growing research on the use of E-Commerce platforms. But in this study, in Tarikolot Village, Bogor, there is no research on village E-Commerce in marketing products from metal craftsmen. Through in-depth interviews, this research aims to uncover this assumption. How will this situation become more productive? Where, how, to what degree and for what reasons can metalworkers affected by COVID-19 use Village E-Commerce. This research gives researchers and practitioners an idea whether E-Commerce applications can be extended to metal craftsmen or even general affected craftsmen. This research builds a web-based Village E-Commerce application architecture through a descriptive research approach by analyzing the results of questionnaires and interviews. This research uses a descriptive model with data sources being in-depth interviews and a scale of E-Commerce business usage in marketing metal products. The importance of this research is the idea of designing a website-based E-Commerce application for managing metal craftsmen products. There are about 400 more metal craftsmen and 200 more metal craftsmen affected by COVID-19. The findings illustrate to researchers and practitioners that the application of E-Commerce can be expanded to improve marketing and market expansion of village metal crafts.